New media, old regimes: case studies in comparative communication law and policy. - Eko, Lyombe S; Eko, Lyombe S (Lexington studies in political communication, 2012)
New Media, Old Regimes: Case Studies in Comparative Communication Law and Policy, by Lyombe S. Eko, is a collection of novel theoretical perspectives and case studies which illustrate how different communication law regimes conceptualize and apply universal ideals of human rights and freedom of expression to media controversies in real space and cyberspace. Eko’s investigation includes such controversial communication policy topics as North African regimes’ failed use of telecommunications to suppress the social change of the Arab Spring, the Mohammad cartoon controversy in Denmark and France, French and American policy of development and diffusion of the Minitel and the Internet, American and Russian regulation of internet surveillance, the problem of managing pedopornography in cyberspace and real space, and other current communication policy cases. This study will aid readers not only to understand different national and cultural perspectives of thorny communication issues, but also show that though freedom of expression is a pluralistic concept, the actions of all political regimes at the national, transnational, and international levels must be held up to the universal standards of freedom of expression set forth in the Universal Declaration of Human Rights. New Media, Old Regimes provides essential scholarship on comparative communication law and policy in a world of new media.